Enzymatic detection of As(III) in aqueous solution using alginate immobilized pumpkin urease: Optimization of process variables by response surface methodology - Talat M.; Prakash O.; Hasan S.H. (My University, 2025)
Urease immobilized on alginate was utilized to detect and quantify As3+ in aqueous solution. Urease from the seeds of pumpkin (vegetable waste) was purified to apparent homogeneity by heat treatment and gel filtration (Sephadex G-200). Further enzyme was entrapped in 3.5% alginate beads. Urea hydrolysis by enzyme revealed a clear dependence on the concentration and interaction time of As3+. The process variables effecting the quantitation of As3+ was investigated using central composite design with Minitab® 15 software. The predicted results were found in good agreement (R2 = 96.71%) with experimental results indicating the applicability of proposed model. The multiple regression analysis and ANOVA showed that enzyme activity decreased with increase of As3+ concentration and interaction time. 3D plot and contour plot between As3+ concentration and interaction time was helpful to predict residual activity of enzyme for a particular As3+ at a particular time. © 2009 Elsevier Ltd. All rights reserved.